Upaya Membangun Kesadaran Bahaya Rokok pada Anak di SDN Kabuaran 1 Bondowoso - Zulfatus Khoirun Nisa’; Dimas Herlambang; Moh Iqbal Hamdani; Azhar Hafizh Musyaffa’; Nayla Inayah Agustin; Kenzie Raffa Sulaiman; Nur Widodo; Listya Purnamasari; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This social project was carried out at SDN Kabuaran 1 with the aim of providing education to 5th and 6th grade students about the dangers of smoking for their health and future. The project was motivated by the low level of awareness among elementary school students regarding the negative impacts of smoking, both physically and socially. The implementation used educational and interactive approaches, such as presentations, group discussions, educational videos. Through this activity, students were expected to understand the harmful effects of smoking on body organs, its environmental impact, and the importance of refusing peer pressure to smoke. The results showed an increase in students’ knowledge and awareness about the dangers of smoking, as seen from their enthusiasm during discussions and question sessions. This project is expected to be an initial step in promoting healthy behavior and instilling positive values from an early age in the school environment.